Entrepreneurial Coenosis in View of Evolutionary Approach - A. N. Kuzminov; V. M. Dzukha; I. G. Paliy (Вестник Российского экономического университета имени Г. В. Плеханова)
The goal of the article is to study current entrepreneurship as economic coenosis being an economic environment, which comes into being during evolution of economic relations. To reach the set goal it is necessary to reveal foundations of inter-disciplinary research of economic processes, to identify evolutionary features of current entrepreneurship functioning and to design basic notions of coenological idea of entrepreneurship leaning on the theory of techno-coenosis. Methodological solution of this problem is possible through identifying general features of complex systems’ shaping – both biological, technical and economic, which are capable of self-organization. The use of coenological approach is grounded in respect of regional entrepreneurship as a type of current economic reality. On the basis of achievements of the theory of systematic, evolution and techno-coenosis the authors provide theoretical and methodological substantiation of using the idea of entrepreneurial coenosis as a new form of the development of complex economic systems. The article shows that the solution of this problem is possible because of the availability of general features, mechanisms of the development, factors and causes of emerging structural and dynamic processes in economic systems with biological, technical and other complex systems characterized by self-organization. By using the example of financial resources, i.e. energy necessary to form the start conditions the logics of evolutionary and population processes of developing regional entrepreneurship was discussed and the algorithm of affecting the relevant economic population was put forward. The obtained findings show that it is necessary to use the coenosis theory in order to describe and analyze the current entrepreneurship as a new objective economic reality, for which evolutionary laws of development are the most important.